2003
DOI: 10.1111/j.1939-1676.2003.tb02431.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Plasma Concentration of Nitric Oxide Metabolites in Dogs with Untreated Mitral Regurgitation

Abstract: Endothelium-dependent (nitric oxide [NO]-mediated) vasodilation is impaired in humans with heart failure. This dysfunction is an important therapeutic target. The plasma concentration of the NO metabolites nitrate and nitrite (collectively referred to as NOx) is a measure of whole-body NO production, provided that the dietary intake of the ions is low. Fifty clinically healthy dogs older than 1 year (median 5.0 years; interquartile interval 2.6-8.2 years) were studied, including 9 controls of various breeds, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 36 publications
4
28
0
Order By: Relevance
“…This result is similar to that of Pedersen et al [19] in which as MMVD severity increased serum nitrotyrosine levels decreased. Medications for congestive heart failure resulting in MMVD, such as pimobendan and ACE-inhibitors, may regulate inflammatory mediators and iNOS expressions.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This result is similar to that of Pedersen et al [19] in which as MMVD severity increased serum nitrotyrosine levels decreased. Medications for congestive heart failure resulting in MMVD, such as pimobendan and ACE-inhibitors, may regulate inflammatory mediators and iNOS expressions.…”
Section: Discussionsupporting
confidence: 81%
“…Nakazawa et al [17] reported that nitrotyrosine concentration was related to cytokine-induced myocardial dysfunction in a canine model, while Cunningham et al [4] reported that mono-nitrogen oxides (NOx) level was positively correlated with NT-pro BNP concentration in dogs with mitral valvular disease or DCM [4,17]. Another study reported that NOx concentration was high in dogs with chronic valvular disease [19].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a reduction in circulating concentrations of nitrate ⁄ nitrite has been reported in dogs in the sub-clinical stages of naturally occurring heart disease (Pedersen et al, 2003). The assumption was that circulating nitrate ⁄ nitrite is reflective of endothelial cell production although the mechanism of this proposed endothelial cell dysfunction has not been investigated.…”
Section: Endothelial Dysfunction and Oxidative Stressmentioning
confidence: 99%
“…Aldosterone participates in the development of structural (remodelling) and functional (endothelial dysfunction) vascular alterations induced by AngII Spironolactone (25 mg ⁄ kg ⁄ day) partially reduces the increased media ⁄ lumen ratio and the impaired response to acetylcholine of resistance arteries in AngII-infused rats Aortic NADPH oxidase activity is increased by AngII and aldosterone and reduced by spironolactone Falk et al (2006) In vivo, dogs with naturally occurring CHF Dogs with naturally occurring myxomatous mitral valve disease have significantly more arterial narrowing in the myocardium, lung and kidney than control dogs Pedersen et al (2003) In vivo, dogs (Cavalier King Charles Spaniels with mitral regurgitation)…”
Section: Endothelial Dysfunction and Oxidative Stressmentioning
confidence: 99%
“…However, investigations of endothelial function in this population have been limited. 14 Noninvasive evaluation of endothelial function can be accomplished via measurement of plasma biomarkers, 6,[15][16][17][18][19][20] endothelium-dependent flow-mediated vasodilation (FMD), 21,22 or assessment of reactive hyperemia (RH). [23][24][25][26] Potential plasma markers of endothelial function include markers of systemic inflammation such as C-reactive protein (CRP) [27][28][29][30] ; markers of nitric oxide (NO) bioavailability such as nitrate and nitrite (NO x ), 15,16,31 L-arginine (L-Arg), asymmetric dimethylarginine (ADMA), and symmetric Abbreviations: 18,19,32,33 ; and indicators of endothelial damage or repair such as von Willebrand factor (vWF) 17,34 or circulating endothelial progenitor cells, 35 respectively.…”
mentioning
confidence: 99%